"As Much Calcium as a Glass of Milk!" Understanding American Consumers' Preferences for Fortified Foods. Issue 1 (2nd January 2017) - Nan, Xiaoli; Verrill, Linda; Iles, Irina
ABSTRACT: This study examines predictors of American consumers' preferences for fortified foods, focusing on sociodemographic as well as psychological correlates. Analysis of a probability-based survey ( N = 6, 728) revealed that females and the more educated tended to have greater preferences for fortified foods. Whites held the least favorable views on fortified foods when compared to Blacks and Hispanics. In terms of psychological predictors, people who were more health-conscious were more likely to prefer fortified foods. Perceived usefulness of nutrition labels and confusion about healthy food choices were both associated with stronger preferences for fortified foods. Both relationships appeared to be moderated by health consciousness. Communication and policy implications of these findings are discussed.